2019
DOI: 10.1104/pp.19.00523
|View full text |Cite
|
Sign up to set email alerts
|

Changing Carrot Color: Insertions in DcMYB7 Alter the Regulation of Anthocyanin Biosynthesis and Modification

Abstract: The original domesticated carrots (Daucus carota) are thought to have been purple, accumulating large quantities of anthocyanins in their roots. A quantitative trait locus associated with anthocyanin pigmentation in purple carrot roots has been identified on chromosome 3 and includes two candidate genes, DcMYB6 and DcMYB7. Here, we characterized the functions of DcMYB6 and DcMYB7 in carrots. Overexpression of DcMYB7, but not DcMYB6, in the orange carrot 'Kurodagosun' led to anthocyanin accumulation in roots. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 49 publications
11
124
0
Order By: Relevance
“…Iorizzo et al identified an R2R3‐MYB gene, DcMYB7 , within the P 3 region as a candidate for the gene controlling anthocyanin biosynthesis in carrot with a purple root and petiole (Iorizzo et al , ). Recently, we confirmed that DcMYB7 is P 3 (Xu et al , ). However, the key gene within the P 1 region that controls anthocyanin biosynthesis in carrot with a purple root and nonpurple petiole is still unknown.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Iorizzo et al identified an R2R3‐MYB gene, DcMYB7 , within the P 3 region as a candidate for the gene controlling anthocyanin biosynthesis in carrot with a purple root and petiole (Iorizzo et al , ). Recently, we confirmed that DcMYB7 is P 3 (Xu et al , ). However, the key gene within the P 1 region that controls anthocyanin biosynthesis in carrot with a purple root and nonpurple petiole is still unknown.…”
Section: Introductionsupporting
confidence: 74%
“…Cavagnaro et al found several QTLs associated with variations in anthocyanin glycosylation and acylation, but did not identify any candidate genes (Cavagnaro et al , ). Following on from that important work, DcUCGXT1 and DcSAT1 , encoding a glycosyltransferase and an acyltransferase, respectively, were found within two QTLs (Xu et al , ). In this study, we confirmed that DcUCGXT1 catalysed the synthesis of Cy3XG by adding xylose to Cy3G and DcSAT1 catalysed the addition of sinapoylglucose to anthocyanins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As expected, we identify several differentially expressed genes (DEG) between the two genotypes known to be involved in carrot root anthocyanin biosynthesis 21,23–26 . Most of the known genes of the pathway and their main regulators were differentially expressed between the two genotypes (Supplementary Table S4).…”
Section: Resultssupporting
confidence: 74%
“…DcbHLH3 , DcUCGXT1 and DcSAT1 ) also displayed no tissue specificity. DcbHLH3 was described as a co-regulator in anthocyanin biosynthesis, while DcUCGXT1 and DcSAT1 participate in anthocyanin glycosylation and acylation, respectively 26,47 . Additionally, seven TFs showed xylem preferential expression-specificity, while only one was preferentially expressed specifically in phloem.…”
Section: Resultsmentioning
confidence: 99%